Prevalence of stroke, associated risk factors and stroke related physical, mental, and economic burden in the Republic of Georgia. (September 2022) - Akhvlediani, Tamar; Gelenidze, Nana; Janelidze, Tamar; Gudadze, Tamar; Pkhakadze, Irine; Webb, Alastair; Katsarava, Zaza
Introduction: We investigated the prevalence, risk factors and physical, mental, and economic consequences of ischemic Janelidze and hemorrhagic stroke in the population of the Republic of Georgia. Materials and Methods: A population-based, cross-sectional study was conducted among 3036 adults residing in the Imereti Region of Georgia, selected using a multistage, probability proportionate-to-size, cluster sampling technique. Data were collected by medical students, using an interviewer-administered questionnaire. Diagnosis of stroke was confirmed by neurologists based on clinical examination and corroborated by documental evidence. Results: Of the targeted 3036 subjects, 2811 (92.6%) participated, of whom 1223 (43.5%) were women. Mean age of the sample was 49.7 (SD 15.2) years. The overall prevalence of stroke was 8.9%, the prevalence of ischemic stroke − 7.8% (95% CI 6.9–8.9) and of hemorrhagic stroke − 0.7% (95% CI 0.4–1.0). Ischemic stroke was more prevalent in males, while hemorrhagic stroke was more prevalent in females. Age, smoking, hypertension, and diabetes were associated with stroke. Stroke victims were young, many of them in the fifth decade of life. Sixty-five percent of them had a modified Rankin scale of three or greater, 25% were depressed, and 85% suffered cognitive impairment. Discussion: Stroke affected people and their families, experiencing a significant economic burden due to loss of the income and increase in out-of-pocket payment for post-stroke medical care. Conclusion: The stroke prevalence in the Republic of Georgia is higher than in Europe and is associated with a significant physical, mental, and economic burden.